Prevalence of permanent pacemaker implantation after conventional aortic valve replacement—a propensity-matched analysis in patients with a bicuspid or tricuspid aortic valve: a benchmark for transcatheter aortic valve replacement. (24th March 2020) - Haunschild, Josephina; Misfeld, Martin; Schroeter, Thomas; Lindemann, Frank; Davierwala, Piroze; von Aspern, Konstantin; Spampinato, Ricardo A; Weiss, Stefan; Borger, Michael A; Etz, Christian D
Abstract: OBJECTIVES: Elective treatment of aortic valve disease by transcatheter aortic valve replacement (TAVR) is becoming increasingly popular, even in patients with low risk and intermediate risk. Even patients with a bicuspid aortic valve (BAV) are increasingly considered eligible for TAVR. Permanent pacemaker implantation (PMI) is a known—frequently understated—complication of TAVR affecting 9–15% of TAVR patients with a potentially significant impact on longevity and quality of life. BAV patients are affected by the highest PMI rates, although they are frequently younger compared to their tricuspid peers. The aim of the study is to report benchmark data—from a high-volume centre (with a competitive TAVR programme) on PMI after isolated surgical aortic valve replacement (SAVR) in patients with BAV and tricuspid aortic valve (TAV). METHODS: We performed a retrospective single-centre analysis on 4154 patients receiving isolated SAVRs (w/o concomitant procedures), between 2000 and 2019, of whom 1108 had BAV (27%). PMI rate and early- and long-term outcomes were analysed. For better comparability of these demographically unequal cohorts, 1:1 nearest neighbour matching was performed. RESULTS: At the time of SAVR, BAV patients were on average 10 years younger than their TAV peers (59.7 ± 12 vs 69.3 ± 9; P < 0.001) and had less comorbidities; all relevant characteristics were equally balanced after statistical matching. Overall PMI rate was significantly higher in BAV patients (5.4% vs 3.8%; P = 0.03). BAV required PMI exclusively (100%) and TAV required predominately (96%) for persistent postoperative high-degree atrioventricular block. After matching, the PMI rate was similar (5.1% vs 4.4%, P = 0.5). In-hospital mortality in the matched cohort was 1% in both groups. Long-term survival was more favourable in BAV patients (94% vs 90% in TAV at 5 years; 89% vs 82% in TAV at 9 years; P = 0.013). CONCLUSIONS: With SAVR, the overall incidence of PMI among BAV patients seems significantly higher; however, after propensity matching, no difference in PMI rates between BAV and TAV is evident. The PMI rate was remarkably lower among BAV patients after SAVR compared to the reported incidence after TAVR.